Pengembangan Media Pembelajaran Interaktif Pada Mata Pelajaran Animasi 2 Dimensi dan 3 Dimensi - Mukhlisulfatih Latief; Agus Lahinta; Maudy Putery Hasan (Jurnal Teknik, 2022)
The absence of interactive learning media that is in accordance with teaching materials and the lack of digital media in animation subjects causes the learning process to be less effective in delivering material, the impact is not achieving learning objectives and decreasing the value of evaluation of basic competencies taken by students. This study aims to 1) develop interactive learning media on 2-dimensional and 3-dimensional animation subjects, 2) to determine the feasibility level of interactive learning media on 2-dimensional and 3-dimensional animation subjects. The method used in this study uses research and development methods by modifying the Borg and Gall models. The results of the interactive learning media validity test by the media validator and material validator obtained very valid results. In the practicality test of the media by the validator, the teacher practitioners obtained very practical results. Likewise, the large group of students obtained very practical results. The results of the effectiveness before and after using the product were based on multiple-choice test instruments, namely the pretest results obtained an average of 60.63 and an average of 84.06 in the posttest which is in the very effective criteria. The conclusion is that interactive learning media on 2-dimensional and 3-dimensional animation subjects meet the level of feasibility, practicality and effectiveness for use in the learning process.